TECHNOLOGY FOR THE DEVELOPMENT OF INCLUSIVE COMPETENCE IN FUTURE SURDOPEDAGOGS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article highlights the content of trends in the development of inclusive education. The introduction of inclusive education , the policy and experience of the field of education at the international level for children with disabilities are emphasized.